Reduction the Effects of the Vibration Parameter on the Replacement Knee Joint during Daily Gait Cycle - Chiad, Jumaa Salman; Yaseen, Noor Dhia; Ghani, Firas Mohammed Abdul (Al-Nahrain Journal for Engineering Sciences, 2018)
There are many patients who face a lot of things that hurt the knee joint. Knee replacement is the best solution to these problems. This research was based on reducing the vibrations of daily activities as measured by the frequency of foot and knee for the patient for three cases when the bare foot, sports shoes with ground air and sports shoes with ground air with silicon damping. Patient information for this work was of age, weight, height and leg length 48 years, 90 kg, 160 cm, 84 cm, respectively. The results was shown that the decline in acceleration results was in the case of sport shoes with ground air with silicon damping with 22.57%, while the decline in vibration results was in the case of sports shoes with ground air with -54.9%.